Mapping educational and training provisions for the museum sector in Portugal: portuguese national report by University of Porto (U.Porto) - Homem, Paula Menino (2017)
Within the Mu.SA Project, this report it's a contribution to the Preparation Working Package, WP2, specifically to the Task T2.3, Mapping educational and training provisions, providing the Mu.SA Consortium with specific information related to the Portuguese context.